1995
DOI: 10.1128/jvi.69.7.4582-4586.1995
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Gag protein composition of a human immunodeficiency virus type 1 vif mutant produced in primary lymphocytes

Abstract: Productive, spreading infection of peripheral blood lymphocytes (PBL) with human immunodeficiency virus type 1 (HIV-1) requires the viral protein Vif. To study the requirement for vif in this system, we infected PBL with a phenotypically complemented HIV-1 clone mutated in vif. Progeny virus was produced which was noninfectious in PBL but replicated in SupT1 cells. Analysis of metabolically labeled proteins of sedimentable extracellular particles made in PBL by radioimmunoprecipitation with either serum from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 34 publications
(102 reference statements)
5
59
0
Order By: Relevance
“…5 and 6) and previous studies suggest that Vif does not affect viral RNA encapsidation (3,40), dimerization, or the stability of the RNA dimer linkage. Altered Gag processing has been demonstrated in vif mutant virions (3,34), raising the possibility that Vif might affect the NC protein, p24 Gag, or the spatial organization of Gag proteins within the nucleoprotein complex and thereby influence reverse transcription. For example, an effect on the NC protein might affect reverse transcription, since in vitro studies have shown that the NC protein decreases the probability of termination of reverse transcription at certain pause sites, enhances strand transfers, promotes selective DNA annealing, and accelerates the renaturation of complementary DNA sequences (20,25,39).…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6) and previous studies suggest that Vif does not affect viral RNA encapsidation (3,40), dimerization, or the stability of the RNA dimer linkage. Altered Gag processing has been demonstrated in vif mutant virions (3,34), raising the possibility that Vif might affect the NC protein, p24 Gag, or the spatial organization of Gag proteins within the nucleoprotein complex and thereby influence reverse transcription. For example, an effect on the NC protein might affect reverse transcription, since in vitro studies have shown that the NC protein decreases the probability of termination of reverse transcription at certain pause sites, enhances strand transfers, promotes selective DNA annealing, and accelerates the renaturation of complementary DNA sequences (20,25,39).…”
Section: Discussionmentioning
confidence: 99%
“…Editing patterns are dominated by GG-to-AG hypermutations, leading to a high frequency of amino acid substitutions and to the introduction of premature STOP codons (Vartanian et al, 1991). These crippled proviruses express aberrant (misfolded/truncated) viral proteins and are unable to produce infectious particles (Simm et al, 1995).…”
mentioning
confidence: 99%
“…Mouse monoclonal antibody (mAb) to EWI-2 (8A12) was a kind gift from Dr. Eric Rubinstein (22). Mouse mAb to HIV-1 p24 (AG3.0) was obtained through the NIH AIDS Reagent Program, Division of AIDS, NIAID, NIH, from Dr. Jonathan Allan (40…”
Section: Antibodiesmentioning
confidence: 99%